Improving Smallholders’ Jobs Through Agribusiness Linkages : Findings of the Mozambique Agricultural Aggregator Pilot (MAAP) - Baxter, Michael; Delgado, Christopher; Romero, Jose Manuel; Walker, Ian (Washington, DC: World Bank, 2022)
Agricultural firms in developing countries may decide to implement aggregation schemes, typically through contract farming arrangements (CFAs). The firms’ rationale for engaging in aggregation is likely to be based on their own anticipated financial gains. But research shows that CFAs can also increase the welfare of their smallholder participants (independent growers). When growers benefit and the CFA terms are set by a firm’s profit-maximizing decisions, the benefits deriving to growers can be seen as “jobs externalities” (i.e. labor income gains to third parties that are triggered by the firms’ actions in expanding the CFAs). The existence of such gains also implies that the aggregation scheme is helping to address market coordination failures by facilitating increased agricultural commercialization. A full appraisal of the impact of CFAs should therefore integrate the analysis of the firms’ and growers’ costs and returns. In this study, we assess the costs and returns to firms and growers from the expansion of seven existing aggregation schemes in Mozambique, using simultaneously gathered data from the firms operating the CFAs, the corresponding CFA participant farmers, and comparable nonparticipant farmers. As far as we know, this is the first attempt at integrated analysis of the impact on firms and independent growers of the expansion of CFAs. Our approach combines impact evaluation and cost-benefit analysis techniques, and yields estimates both of the financial returns to firms and of the CFAs’ full social returns (including the gains to the growers and to society at large). In most cases, we found that the growers gained more than the firms in the short term from the expansion of these schemes. In fact, growers’ incomes increased (relative to the comparators) in most of the schemes we analyzed. However, only half the schemes generated profits for the firms themselves in the three year time window of this study. This poor short-term financial return to the aggregator firms may explain why CFAs have expanded less than would seem to be justified when the gains to growers are factored in. These findings might justify a public subsidy to catalyze the expansion of CFA schemes that are expected to be financially viable in the medium term. We estimated the subsidy amount that would be needed to raise the firms’ private returns to the market cost of capital (a benchmark for financial viability from the firms’ perspective). We found that the required subsidy was normally modest: it averaged less than 25 per cent of the firms’ expenditures on supporting new growers. Overall, our results support the case for the selective use of public resources to catalyze an expansion of aggregator systems in Mozambique and similar economies, and thereby improve smallholder growers’ welfare.